Biophysical and molecular modelling analysis of the binding of β-resorcylic acid with bovine serum albumin. (February 2023) - Hussain, Irfan; Fatima, Sana; Ahmed, Shahbaz; Tabish, Mohammad
Abstract: The bovine serum albumin (BSA) is a model carrier protein that transports and deposits the various endogenous and exogenous ligands in the body. β-resorcylic acid (BR) is a phyto-phenolic molecule mainly used in the food industry because of its antibacterial, flavouring and preservative nature. The interactions of small ligand molecules with proteins are of great importance for researchers from the pharmacology perspective. This article explains the mechanism of binding of BR with BSA with the help of multi-spectroscopic approaches and molecular modelling. The UV absorption and fluorescence spectroscopy affirmed the formation of BSA-BR complex. The thermodynamic studies confirmed the nature of the reaction to be spontaneous and exothermic, and the stabilisation of the complex by van der Waals interactions and hydrogen bonding. The energy transfer was found to occur with a high probability. BR induced the microenvironmental and conformational alterations BSA as revealed by synchronous spectra, 3D fluorescence maps, circular dichroism (CD), resonance-enhanced Rayleigh scattering (RRS), red edge excitation shift ( REES) and Fourier transform infrared (FT-IR). The β-cyclodextrin (β-cd), metals and vitamins largely influenced the BR-BSA binding strength. Competitive displacement assays further elucidated the BR binds to BSA at subdomain IIIA (site II). Molecular docking and simulations computationally validated the results of the wet lab experiments. Graphical abstract: Image 1 Highlights: The BSA-BR complex was affirmed with 1:1 binding stoichiometry and quenching in static mode. The binding reaction was spontaneous and exothermic, involving van der Waals forces and hydrogen bonding. The binding strength was found to change in the presence of metal ions, vitamins and β-cd. BR binds with BSA near subdomain IIIA (site II). BR induced minor changes in the conformation and microenvironment in BSA.